The Impact of ChatGPT Use on the Quality of Academic Support for Students - Wibowo, Guntur Arie; Rahman, Aulia; Anis, Madhan (Technology and Society Perspectives (TACIT), 2023)
The development of technology has had a significant impact on the education sector. The use of technology, including ChatGPT, as a tool in providing academic support for students is becoming increasingly common. This study aims to analyze the impact of using ChatGPT on the quality of academic support for students. This research is a literature review using a qualitative approach, which means that it will analyze and interpret data using information and text from a variety of different sources. The study results show that the use of ChatGPT in student academic support has a significant impact on accessibility and learning efficiency. Although it provides easy access to information, it should be noted that irreplaceable human interaction remains important. The development of this technology requires wise integration, focusing on training education-specific models and involving teachers in continuous monitoring and development.